1994
DOI: 10.1080/15287399409531880
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of four potentially ichthyotoxic marine phytoflagellates determined by four different test methods

Abstract: The toxicity of the marine phytoflagellates Prymnesium parvum. Prymnesium patelliferum, Chrysochromulina polylepis, and Chrysochromulina leadbeateri isolated from ichthyotoxic blooms in Norwegian coastal waters was compared using four different test methods developed for the detection of toxins produced by these species. The test methods were (1) lethality to the crustacean Artemia salina exposed to living algae, (2) hemolytic activity (lysis of human erythrocytes) by crude algal lipid extracts, and inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…Previous studies have shown that limiting conditions of either nitrogen or phosphorus enhance the toxic effect of Prymnesium parvum (Shilo 1971, Meldahl et al 1994, Johansson & Granéli 1999, suggesting that toxin production is a defence mechanism used to improve the competitive ability of P. parvum under conditions of severe nutrient competition. In the present study we investigated the survival and feeding of the ciliate Euplotes affinis, when exposed to mixed cultures of P. parvum and Rhodomonas cf.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that limiting conditions of either nitrogen or phosphorus enhance the toxic effect of Prymnesium parvum (Shilo 1971, Meldahl et al 1994, Johansson & Granéli 1999, suggesting that toxin production is a defence mechanism used to improve the competitive ability of P. parvum under conditions of severe nutrient competition. In the present study we investigated the survival and feeding of the ciliate Euplotes affinis, when exposed to mixed cultures of P. parvum and Rhodomonas cf.…”
Section: Introductionmentioning
confidence: 99%
“…In Prymnesium spp., laboratory experiments indicate that toxin production is enhanced under nutrient stress irrespective of which nutrient (N, P) is limiting growth (Johansson and Granéli 1999). Phosphorus limitation stimulates the toxicity of P. patelliferum compared to nutrient-replete conditions (Larsen et al 1993;Meldahl et al 1994;this study). Because N and P are minor elements in the composition of the toxin complex (e.g., prymnesins) found in ichthyotoxic haptophytes (Igarashi et al 1996), it has been hypothesized that the toxicity in haptophytes such as Chrysochromulina and Prymnesium spp.…”
mentioning
confidence: 99%
“…(Edvardsen and Paasche 1998). Nutrient availability seems to be an important regulation factor for the production of different types of algal toxins (Anderson et al 1990;Bates et al 1991;McLachlan et al 1994;Meldahl et al 1994;Johansson and Granéli 1999). In Prymnesium spp., laboratory experiments indicate that toxin production is enhanced under nutrient stress irrespective of which nutrient (N, P) is limiting growth (Johansson and Granéli 1999).…”
mentioning
confidence: 99%
“…Other plankton organisms were also shown to be affected by this Chrysochromulina bloom (Nielsen et al 1990). Chrysochromulina leadbeatri caused mortalities in caged salmon among the northern Norwegian coast in 1991 and the two Prymnesium (P. patelliferum and P. parvum) have also caused mortalities in aquaculture facilities for salmon and rainbow trout (Aune et al 1992;Meldahl et al 1994Meldahl et al , 1995.…”
Section: Other Types Of Toxic Bloommentioning
confidence: 99%